Dimethyl Fumarate Protects against Lipopolysaccharide- (LPS-) Induced Sepsis through Inhibition of NF-κB Pathway in Mice - He Fang; Xingtong Wang; Mahendra Damarla; Rongju Sun; Qingli He; Ruojing Li; Pengfei Luo; Jun O. Liu; Zhaofan Xia (Hindawi Limited, 2023)
Sepsis is one of the most severe complications and causes of mortality in the clinic. It remains a great challenge with no effective treatment for clinicians worldwide. Inhibiting the release of proinflammatory cytokines during sepsis is considered as an important strategy for treating sepsis and improving survival. In the present study, we have observed the effect of dimethyl fumarate (DMF) on lipopolysaccharide- (LPS-) induced sepsis and investigated the possible mechanism. By screening a subset of the Johns Hopkins Drug Library, we identified DMF as a novel inhibitor of nitric oxide synthesis in LPS-stimulated RAW264.7 cells, suggesting that DMF could be a potential drug to treat sepsis. To further characterize the effect of DMF on LPS signaling, TNF-α, MCP-1, G-CMF, and IL-6 expression levels were determined by using cytokine array panels. In addition, an endotoxemia model with C57BL/6 mice was used to assess the in vivo efficacy of DMF on sepsis. The survival rate was assessed, and HE staining was performed to investigate histopathological damage to the organs. DMF was found to increase the survival of septic mice by 50% and attenuate organ damage, consistent with the reduction in IL-10, IL-6, and TNF-α (inflammatory cytokines) in serum. In vitro experiments revealed DMF's inhibitory effect on the phosphorylation of p65, IκB, and IKK, suggesting that the primary inhibitory effects of DMF can be attributed, at least in part, to the inhibition of phosphorylation of IκBα, IKK as well as nuclear factor-κB (NF-κB) upon LPS stimulation. The findings demonstrate that DMF dramatically inhibits NO and proinflammatory cytokine production in response to LPS and improves survival in septic mice, raising the possibility that DMF has the potential to be repurposed as a new treatment of sepsis.